Parkinson's disease and the COVID-19 pandemic: responding to patient need with nurse-led telemedicine. (2nd June 2020) - Thomas, Sue; Mancini, Francesca; Ebenezer, Louise; Price, Jane; Carta, Tania; Cordasco, Jessica; Tedesco, Chiara; Gillett, Sarah
Abstract : With the COVID-19 pandemic limiting face-to-face interaction, the drive for innovation and the need to develop alternative solutions to patient engagement, treatment and diagnosis has been suddenly accelerated. Sue Thomas and national and international colleagues outline a novel technological initiative launched in Italy to cope with the pressures of the pandemic, providing inspiration for similar future projects in the UK